2019
DOI: 10.1177/1356766719858649
|View full text |Cite
|
Sign up to set email alerts
|

Food tourism value: Investigating the factors that influence tourists to revisit

Abstract: Food consumption is an important notion in the hospitality literature. Although its role in gaining visitors’ satisfactory travel experience and in affecting tourists’ experiences of a destination is acknowledged, the impact of travelers’ local food consumption value on tourist behavior remains an underdeveloped topic. This study investigated the effect of tourists’ local food consumption value on their future behaviors by focusing on their destination food image and their attitudes toward local food. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
5
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(174 citation statements)
references
References 129 publications
11
128
5
4
Order By: Relevance
“…Within the last few decades, in spite of the wide range of diverse and unique cultural and natural attractions, the Iranian tourism industry has been continuously facing significant challenges (Seyfi & Hall, 2018). In particular, while previous food tourism research highlights the potential of Iranian cuisine as a major influence on tourists' experiences (Rousta & Jamshidi, 2019; Torabi Farsani, Zeinali, & Moaiednia, 2018), so far the Iranian tourism industry has had little progress in the widespread development and marketing of food‐tourism products (Sayadabdi & Hassibi, 2018; Torabi Farsani et al, 2018). Nevertheless, Iran presents distinctive and attractive food attractions to international and domestic visitors.…”
Section: Methodsmentioning
confidence: 99%
“…Within the last few decades, in spite of the wide range of diverse and unique cultural and natural attractions, the Iranian tourism industry has been continuously facing significant challenges (Seyfi & Hall, 2018). In particular, while previous food tourism research highlights the potential of Iranian cuisine as a major influence on tourists' experiences (Rousta & Jamshidi, 2019; Torabi Farsani, Zeinali, & Moaiednia, 2018), so far the Iranian tourism industry has had little progress in the widespread development and marketing of food‐tourism products (Sayadabdi & Hassibi, 2018; Torabi Farsani et al, 2018). Nevertheless, Iran presents distinctive and attractive food attractions to international and domestic visitors.…”
Section: Methodsmentioning
confidence: 99%
“…TCV assumes that consumer preferences are affected by multiple pre-consumption cues, namely the potential functional, emotional, social, or epistemic value a product or service is perceived as holding. The prominence of each source of value is contingent upon the consumption situation (Rousta and Jamshidi, 2020). For example, while functional value has traditionally been considered the major factor shaping consumer decisionmaking (Williams and Soutar, 2009) it nevertheless includes a range of characteristics (e.g., quality, price, usefulness) (Perrea et al, 2015).…”
Section: Consumption Value Theory (Tcv)mentioning
confidence: 99%
“…Rasht boasts significant food diversity when compared to other cities in Iran and is the only Iranian city recognized by UNESCO (2015) as a creative food city, with this designation attracting food tourists in significant numbers (Mehrabadi et al, 2017). Further, Rasht is known for various different types of local food products, each well-known enough to influence tourist decisionmaking and behaviors (Rousta and Jamshidi, 2020). As such, the city has the potential to draw upon its culinary heritage for promotion purposes; opening the door for significant sustainable tourism development and the associated economic boon in the process (MacKenzie & .…”
Section: Study Contextmentioning
confidence: 99%
“…Value has been conceptualized as what people get for what they give, such as a trade-off between the perceived gains and the sacrifices (Zeithaml, 1988). Many studies have revealed consumer value as an underlying determinant for consequent variables, such as affective responses, which include attitude and satisfaction, and consumption behaviors across the settings (Bilgihan and Bujisic, 2015; Chua et al, 2019; Kim et al, 2017b, 2019; Lee and Kim, 2018; Rousta and Jamshidi, 2020). It is accordingly perceived as an indispensable concept to understand the consumers’ behavioral intentions with hospitality.…”
Section: Literature Reviewmentioning
confidence: 99%